Caracterización del Sistema de Tenencia y el Perfil Hematológico - Bioquímico de la Gallina Criolla Ecuatoriana en la Provincia de Cotopaxi. - Coyago Quishpe, Erika Silvana (2018)
The research project was done in the province of Cotopaxi in Latacunga, Salcedo, Saquisilí and Pujilí, cantons to determine the main characteristics of the tenancy system and the hematological and biochemical reference values of the Ecuadorian natural hen, as bases for its conservation and genetic improvement. To characterize the tenancy system, 100 surveys applied to the producers; the main aspects collected in the survey were general data of the owner, history of the exploitation, human data, management of the natural hen and veterinary attention, 30 natural hens (18 hens and 12 roosters) were used. The hematological variables (hematocrit, hemoglobin, erythrocytes, VGM, MCH, CGMH, platelets, leukocytes, relative and absolute values) were evaluated in the biochemical profile (glucose, urea, BUN, creatinine, total proteins, AST, ALT, calcium phosphorus and potassium). The statistics included a descriptive analysis of the data resulting from the survey and an analysis of variance (ANOVA) with the Tukey multiple comparisons method with measures of arithmetic mean (Mean) and standard deviation (Standard deviation) to establish differences between males and females for the variables under study. 71% of the population dedicated to the breeding of natural chickens are women and 29% men, with an average age of 47 years with inferior studies. The total population of natural hens represents with 33.67% of the offspring, 53.51% of the hens and 12.82% of the roosters. In relation to sex, hematocrit variables (M 45.52 ± 1.98) - (H 37.88 ± 1.62), hemoglobin (M 14.78 ± 0.66) - (H 12.26 ± 0, 54) and erythrocytes (M 4.50 ± 0.19) - (H 3.88 ± 0.16b) showed significant differences, favorable to males. Sexual dimorphism was observed in favor of the females, in the chemical profile, particularly for the variable calcium (H 3.90 ± 0.27) - (M 2.64 ± 0.33).